2021
DOI: 10.1002/htj.22070
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the loop thermosyphon with different adiabatic lengths charged with different working fluids

Abstract: This paper reports an experimental investigation of a closed‐loop thermosyphon system charged with water and other low saturation fluids, such as ethanol, acetone, and methanol, for different adiabatic lengths, filling ratios, and heat loads. The closed‐loop thermosyphon with two inline vertical heaters in the evaporator section and forced air‐cooled plate‐type heat exchanger in the condenser section, connected by a changeable adiabatic length, is investigated at different working conditions. Out of five filli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The heat transmission coefficient of 2456 W/m2.°C is greater than that of the preceding two types.. When compared to other fluids, the efficiency and low values (up to 72% reduction in total thermal resistance) of an acetone-charged loop thermosyphon were striking [26]. The plate-type forced air-cooled condenser had the maximum heating and cooling efficiency.. Because of this, the loop thermosyphon with a plate-type forced air-cooled condenser was seen as an adequate solution to the problem of overheating in electronic components, computer clusters, and data centers when using a water-cooled condenser.…”
Section: Introductionmentioning
confidence: 87%
“…The heat transmission coefficient of 2456 W/m2.°C is greater than that of the preceding two types.. When compared to other fluids, the efficiency and low values (up to 72% reduction in total thermal resistance) of an acetone-charged loop thermosyphon were striking [26]. The plate-type forced air-cooled condenser had the maximum heating and cooling efficiency.. Because of this, the loop thermosyphon with a plate-type forced air-cooled condenser was seen as an adequate solution to the problem of overheating in electronic components, computer clusters, and data centers when using a water-cooled condenser.…”
Section: Introductionmentioning
confidence: 87%
“…2 score of the DT model was 98.504; whereas, the R 2 score of the RF model and linear regression model were about 94.76 and 92.17, respectively.…”
mentioning
confidence: 91%
“…For the performance, reliability, and lifespan of the components, thermal management of the cooling devices is very important so that these devices should work within the safe temperature range. 1,2 The study of CLT and its performance has been carried out by different researchers theoretically, experimentally, and numerically. But, the machine learning (ML) approach is not yet used in the CLT system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that with the increase in m e / m c , the HPHE's effectiveness and heat transfer rate increased. At different adiabatic lengths, filling ratios, and heat fluxes, a two‐phase thermosyphon loop was investigated by Birajdar and Sewatkar 20 using methanol, ethanol, water, and acetone as working fluids. Results demonstrated that the filling ratio of 0.6 showed higher performance.…”
Section: Introductionmentioning
confidence: 99%